2023
DOI: 10.3389/fvets.2022.1102424
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and etiology of dentoalveolar trauma in 1,592 United States military working dogs: A 1-year retrospective study

Abstract: The objective of this study was to quantify the overall prevalence and classification of traumatic dentoalveolar injury (TDI) in a large population of military working dogs (MWDs). The medical records of 1,592 MWDs undergoing routine oral exam and periodontal treatment over a 1-year period were reviewed. The MWDs were located at over 100 military veterinary treatment facilities across the globe. Patient signalment, occupational duty certification, tooth injured, and trauma etiology were recorded. The overall p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…The prevalence of dental injuries in our report (19.8%) was lower than a recent study by Bilyard et al 16 on dental trauma in a population of US MWDs, which found that the 1-year prevalence of traumatic dental injury was 43.6% (n = 596). 16 However, our study included only dental injuries that resulted in lost duty days and thus was not a comprehensive measure of all dental issues. This likely resulted in a lower respective prevalence of dental injuries.…”
Section: Discussioncontrasting
confidence: 87%
“…The prevalence of dental injuries in our report (19.8%) was lower than a recent study by Bilyard et al 16 on dental trauma in a population of US MWDs, which found that the 1-year prevalence of traumatic dental injury was 43.6% (n = 596). 16 However, our study included only dental injuries that resulted in lost duty days and thus was not a comprehensive measure of all dental issues. This likely resulted in a lower respective prevalence of dental injuries.…”
Section: Discussioncontrasting
confidence: 87%
“…A 1‐year retrospective study in military working dogs from the United States reported that the overall prevalence of traumatic dentoalveolar injury was 43.6%, with a mean number of injuries per dog of 1.2. In this study, maxillary tooth fractures were more frequent than mandibular tooth fractures; incidental findings with an unknown cause accounted for most tooth trauma, followed by housing, bite work and blunt force trauma 14 . Another study revealed dentoalveolar injuries were common among dogs and cats with maxillofacial fractures.…”
Section: Discussionmentioning
confidence: 56%
“…In this study, maxillary tooth fractures were more frequent than mandibular tooth fractures; incidental findings with an unknown cause accounted for most tooth trauma, followed by housing, bite work and blunt force trauma. 14 Another study revealed dentoalveolar injuries were common among dogs and cats with maxillofacial fractures. The authors pointed out that age and trauma mechanisms were significant predictors of dentoalveolar injuries in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth fractures and periodontal diseases were the most common dental diseases. Traumatic dental injuries, including tooth fractures, can result from a variety of factors such as training, housing or environmental conditions, and behavior [ 19 , 20 ]. While the number of cases evaluating the causes of dental injuries in the medical records of AFMRI was limited, tooth fractures in Korean MWDs may be also related to a similar etiology.…”
Section: Discussionmentioning
confidence: 99%